1971
DOI: 10.1039/c29710000875
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray crystal structure of µ-5-cyclopentadienylcyclopentadiene-bis-(π-cyclopentadienylplatinum)-Pt–Pt

Abstract: The product of the reaction between C,H,Na and PtC1, is shown by X-ray crystal structure analysis to consist of two n-cyclopentadienylplatinum units joined by a Pt-Pt bond and a bridging 5-cyclopentadienylcyclopentadiene unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…-Mononuclear transition metal-complexes of 1,3-dienes are well documented [l] [2]. In contrast, only a limited number of complexes of 1,3-dienes bonded to two [3] or more [4] adjacent metal centres have been reported. Although the synthetic methods for such species are not yet general and newer ones need to be developed, it is thinkable that the chemistry of these dinuclear complexes should become as interesting and useful as that of their monometallic analogues.…”
Section: 2l]heptan-7-ane)]bis(tricarbonyliron) (13)mentioning
confidence: 99%
“…-Mononuclear transition metal-complexes of 1,3-dienes are well documented [l] [2]. In contrast, only a limited number of complexes of 1,3-dienes bonded to two [3] or more [4] adjacent metal centres have been reported. Although the synthetic methods for such species are not yet general and newer ones need to be developed, it is thinkable that the chemistry of these dinuclear complexes should become as interesting and useful as that of their monometallic analogues.…”
Section: 2l]heptan-7-ane)]bis(tricarbonyliron) (13)mentioning
confidence: 99%
“…Solvent was decanted from the yellow precipitate which was washed with diethyl ether (2 x 20 cm3), and dried in uacuo to give yellow microcrystals of [Pt(q-C2H4)(q2-C5H6)(q-C5Hs)]-[BF4] (5) (0.41 g , 93%) (Found: C, 32.6; H, 3. (1) with Dipheny1acetyIene.-A solution (4) with PhC-CPh .-Freshly sublimed Me,NO (0.038 g, 0.5 mmol) was added to a stirred solution of (4) (0.144 g, 0.25 mmol) and diphenylacetylene (0.178 g, 1 mmol) in dry acetone (25 cm3). The mixture was stirred at room temperature for 12 h, the colour changing from red to dark green.…”
Section: Reaction Of Di-p-chloro-dichlorobis(rpethy1ene)diplatinum Wi...mentioning
confidence: 99%
“…[4,5] Similar examples of NaCp acting as as equential reductant and trapping agent can be found in the literature. [9] In one canonical report by Wilkinson and co-workers,i tw as found that the reaction of ReCl 5 with NaCp led to the formation of the Re III complex Cp 2 ReH, as well as,p resumably,a ne quivalent of coupled Cp (i.e. DHF).…”
mentioning
confidence: 99%